Greckie wyrazy βόρατον, βράθυ, βουρί jako przykłady zapożyczenia wielokrotnego - Kaczyńska, Elwira (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The paper discusses three Ancient Greek appellatives βόρατον, βράθυ, βουρί denoting conifers from the Cupressaceae family and demonstrates a common Semitic origin of these dendronyms. They should be treated as examples of multiple borrowing, the ultimate source of which was the uniform Proto-Semitic archetype *burāṯ- ‘juniper, Juniperus L.’. It should be assumed that the ancient Greeks borrowed two synonymous terms βόρατον n. ‘stinking juniper, Juniperus foetidissima Willd.; savin juniper, Juniperus sabina L.’ and βράθυ n. ‘id.’ from two different Aramaic sources. On the other hand, the Pamphylian dialectism βουρί n. ‘Mediterranean cypress, Cupressus sempervirens L.’ was borrowed from an Akkadian source via Anatolian languages to Ancient Greek (Gk. Pamph. βουρί n. ‘cypress’ ← Lycian *burhi < *burehi < Luwian *burašiš c. ← Assyrian or Akkadian burāšu ‘(Phoenician) juniper’ < Old Akkadian burāšum ‘juniper’ < Proto-Semitic *burāṯ-). A carefully conducted analysis of lexical data clearly demonstrates that language contacts between the Semites and the Greeks took place at different times and in many places, so potential Semitisms could have gradually penetrated the Greek vocabulary by various ways.